Education and youth re-orientation: a panacea for lasting peace in Nigeria’s Niger Delta region (2009)
The Niger Delta region of Nigeria has been a hot bed of political and economic agitations in the last 10 years. Though the agitations which began in 1966 by late Major Adaka Boro has in the last decade assumed wider significant dimensions which threatens the peaceful coexistence of the One hundred and fifty million Nigerian that live in the entity called Nigeria. The causes of agitation is traceable to the availability of rich oil and gas deposits in the Niger Delta region accounting for almost 90% of Nigeria’s gross total foreign exchange earnings in the last four decades. Despite the abundance of these resources, the region has felt marginalized and requested for a fair share of the nations resources. The military with its totalitarian nature in previous Nigerian governments have often scuttled every attempt for legitimate agitation. The advent of Democracy in Nigeria in 1999 resurfaced the struggle for resource control in the region. This paper reviews the cause of the Niger Delta struggle seen as political marginalization, social deprivation and economic exploitation in a federating environment. Solutions featuring political solutions, economic evolution and social regeneration of the region have been recommended. Useful suggestions to educational planners have been provided.